Implementasi Penerbitan Healthbook TB. Pacific Star II pada Karantina Dumai oleh PT. Berlian Ocean Shipping - Sabila, Fadiyah Hani; Gultom, Dika Praza (JURNAL BARTEK, 2026)
The issuance of a Health Book (Ship's Health Book) is a crucial component of the health quarantine monitoring system at international ports to prevent the spread of infectious diseases across borders. This study aims to analyze the implementation of Health Book issuance procedures for the vessel TB. Pacific Star II, managed by PT. Berlian Ocean Shipping within the operational area of the Class I Health Quarantine Office in Dumai. The research method used is descriptive qualitative, with data collection techniques through participatory observation during field practice, interviews, and documentation studies. The results indicate that the issuance process involves a series of physical ship inspections, crew document validation, and the use of the digital feature "Sinkarkes." Although procedures follow regulations, several technical obstacles were found, such as internet network instability in the port area and system limitations that hinder real-time data synchronization. Optimization efforts are carried out through intensive coordination between the agent and quarantine officers, along with proposals for developing offline features in the Sinkarkes system. This study concludes that the smooth issuance of the Health Book highly depends on the readiness of ship documents and the stability of the information technology infrastructure at the port.